2017
DOI: 10.18280/ijht.35sp0134
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art and future development of sensible heat thermal electricity storage systems

Abstract: Wind and solar energy have a variable and intermittent nature, a characteristic which forces fossil fuel thermal power plants to be used as backup units for grid stabilization. The development and installation of large-scale cost-effective energy storage systems is necessary to adapt electricity generated by renewables to the users' demand. But, the installation of conventional energy storage can add new capacity and further reduce the thermal power plants operational utilization factor. For these reasons, Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, being electricity demand instantaneously balanced 24/7, huge and unpredictable power changes can be the source of imbalances between supply and demand that can provoke grid damage, user devices fault or blackouts. These unpleasant effects can be managed and/or limited using fossil fuels power plants working in cycling operation mode and energy storage units (see e.g., [7][8][9][10][11][12][13][14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%
“…However, being electricity demand instantaneously balanced 24/7, huge and unpredictable power changes can be the source of imbalances between supply and demand that can provoke grid damage, user devices fault or blackouts. These unpleasant effects can be managed and/or limited using fossil fuels power plants working in cycling operation mode and energy storage units (see e.g., [7][8][9][10][11][12][13][14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as stated in several research works (see, e.g., [10][11][12][13][14][15][16]), to prevent such damaging situations, fossil fuel power stations need to be used as back-up units, and electricity energy storage systems need to be installed.…”
mentioning
confidence: 99%
“…According to their findings, the RTE of helium is greater, and at the isentropic conditions and greater pressure ratios, the energy storage performance increases. The charging process involved the use of an electric heater in a plant designed by Benato et al [27,28,43]. Moreover, a packed-bed (one-dimensional, two-phase) model is also developed, where two heat transfer fluids are tested along with nine heat storage materials.…”
Section: Joule-brayton Ptes Thermodynamic Cyclementioning
confidence: 99%
“…Heat engine expander and heat pump compressor components are used by Rankine PTES systems, and they are usually separated in standard configurations. Several studies have suggested that reversible configurations could be used in order to reduce investment costs [37][38][39][40][41][42][43][44].…”
Section: Conventional Rankine Cyclesmentioning
confidence: 99%